IMPLEMENTING MENTAL HEALTH AWARENESS CAMPAIGNS TO REDUCE STIGMA AND PROMOTE HELP-SEEKING BEHAVIOR - Metab Ajaj Al Onazi, Abdullah Saud Alyousef, Faizah Masad Salman Alzaidi, Abdullah Saud Alyousef, Nasser Hammad Mohammad Aldosari, Salma Ali Saleh Aldarbi, Malak Yahyaa Jaribi, Mobarak Ali Mohamad Aldosari,; Abdullah Saud Alyousef Alotaibi, Rubayyi Abdullah Shabib Alqahtani, Sara Mohammad Alhezaim, Mushael Mohammad Saad Al Hammad (Chelonian Research Foundation, 2022)
It is concerning that the prevalence of mental health issues among adolescents is on the rise. Adolescents who require mental health assistance the most are hesitant to do so. Further comprehension regarding the assistance sought by this demographic is required in order to bridge this divide. A search was conducted across five databases in order to identify the primary obstacles, enablers, and interventions that target the seeking of assistance for prevalent mental health issues among adolescents aged 10–19 years. The chief obstacles frequently mentioned were stigma and unfavorable perceptions of mental health professionals and services. The facilitators possessed prior favorable encounters with mental health literacy and health services. The majority of interventions relied on psychoeducation, which centered on topics such as stigma, melancholy, suicide and self-harm, and general mental health knowledge. Additional forms of interventions encompassed outreach initiatives, peer training, and the utilization of online and multimedia resources. In general, the studies yielded results of moderate to low quality, and there was a lack of consensus concerning the definition and metrics of help-seeking. Despite the fact that the majority of interventions occurred in educational environments, it is crucial to consider adolescents who are not enrolled in school. The provision of greater access to mental health services to all adolescents in need should incentivize them to seek assistance; however, Child and Adolescent Mental Health Services continue to face a significant obstacle in this regard. Furthermore, research pertaining to help-seeking behaviors among adolescents must establish more rigorous methodological standards, incorporate shared definitions, and construct theoretical frameworks. By increasing the consistency and generalizability of findings, this will facilitate the advancement of interventions that encourage individuals to seek assistance, as well as guarantee prompt availability of treatment for psychological disorders. Keywords: mental health awareness, child, adolescent, psychological disorders, review.